The Effect of Academic Environment and Financial Literacy on the Accounting Competence of Vocational School Students in DKI Jakarta with Self-Efficacy as a Mediating Variable - Shofiany; Ari Saptono; Suparno (Journal of Digital Business and Global Economy, 2026)
Shofiany. 1716823012. The Impact of Academic Environment and Financial Literacy on the Accounting Skills Competence of Vocational High School Students in DKI Jakarta, with the mediating variable being self-efficacy. thesis. Jakarta State University, Faculty of Economics and Business, Master of Economics Education, 2025. Using self-efficacy as a mediating variable, this study seeks to examine the influence of the academic environment and financial literacy on the accounting skills competency of vocational high school students in DKI Jakarta. The fundamental basis of this research is on the significance of the learning environment's quality and financial literacy skills in developing students' proficiency in accounting, particularly in an era marked by increasingly intense job competition. The employed research methodology was a quantitative approach utilizing a survey technique. The research cohort comprised 207 pupils from three public vocational institutions in Jakarta, chosen through proportional random sampling. A questionnaire that has been verified for correctness and consistency was used to gather information. The data was examined employing partial least squares structural equation modeling, or PLS-SEM. The findings demonstrated that the academic environment exerted a positive and significant influence on students' self-efficacy and proficiency in accounting skills. It was also demonstrated that financial literacy improved competence through self-efficacy, both directly and indirectly. Furthermore, the connection between the academic setting and financial literacy on accounting skills competence is strengthened by self-efficacy acting as a mediating element. These results suggest that raising the quality of the educational setting and strengthening financial literacy need to be carried out continuously to improve students' competency in the field of accounting.